School Construction Strategies for Universal Primary Education in Africa : Should Communities Be Empowered to Build their Schools? - Theunynck, Serge (World Bank, 2012)
This book examines the scope of the infrastructure challenge in Sub-Saharan Africa and the constraints to scaling up at an affordable cost. It assesses the experiences of African countries with school planning, school facility designs, construction technologies, and construction management over the past thirty years, and draws lessons on promising approaches to enable African countries to scale up the facilities required to achieve the Education for All (EFA) goals and Millennium Development Goals (MDGs) of complete quality primary education for all children at the lowest marginal cost. The book is organized along the following lines. Chapter one reviews the nature and scope of the primary school infrastructure challenges. Chapter two reviews the experience of African countries with school planning and resource allocation norms and how they have affected the volume, functionality, and distribution of primary school facilities. Chapters three, four, and five examine the impact of construction technology and approaches to construction management on the cost of school infrastructure and the ability to scale up. Chapter six delves more deeply into how to set up one of the most cost- effective approaches to school provision the community-based approach. Chapter seven looks at maintenance issues. Chapter eight deals with corruption and chapter nine with donors. Chapter ten provides an estimate of the infrastructure cost of the EFA challenge and recommendation for countries and donors to improve the efficiency of the resources spent for school construction.